Expanding the phosphorus–carbon analogy: formation of an unprecedented 5-phosphasemibullvalene derivative. Issue 44 (22nd April 2016) - Rigo, Massimo; Weber, Manuela; Müller, Christian
Abstract : The selective and quantitative photochemical di-π-methane rearrangement of a phosphabarrelene allows access to the first 5-phosphasemibullvalene derivative. Abstract : We could access for the first time a 5-phosphasemibullvalene derivative via quantitative and selective photochemical di-π-methane rearrangement from the corresponding phosphabarrelene. Due to the striking analogy between phosphorus and carbon, this hitherto unknown transformation of vinyl-phosphorus species provides the possibility to prepare novel, chiral and conformationally rigid organophosphorus cage compounds in a straightforward manner.